2021
DOI: 10.1177/09544062211062452
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic aerodynamic analysis for compressor blades with manufacturing variability based on a mathematical dimensionality reduction method

Abstract: It is essential for engineering manufacture and robust design to evaluate the impact of manufacturing variability on the aerodynamics of compressor blades efficiently and accurately. In the paper, a novel quadratic curve approximation method based on the scanning points of blade design profiles was introduced and combined with Karhunen–Loève expansion, a mathematical dimensionality reduction method for modeling manufacturing variability as truncated Normal process was proposed. Subsequently, Sparse Approximati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…When the total number of workpieces is large enough, the geometric deviation distribution based on the Gaussian process is in good agreement with the actual machining deviation measurement data. 16,26 Therefore, under the machining deviation uncertainty influence, this work considers that the thickness deviation value also obeys the Gaussian distribution. UQ analysis of the influence of thickness deviation on compressor performance under the 1st-level and the 3rd-level machining accuracy is carried out.…”
Section: Blade Model Construction Methodsmentioning
confidence: 99%
“…When the total number of workpieces is large enough, the geometric deviation distribution based on the Gaussian process is in good agreement with the actual machining deviation measurement data. 16,26 Therefore, under the machining deviation uncertainty influence, this work considers that the thickness deviation value also obeys the Gaussian distribution. UQ analysis of the influence of thickness deviation on compressor performance under the 1st-level and the 3rd-level machining accuracy is carried out.…”
Section: Blade Model Construction Methodsmentioning
confidence: 99%
“…The calculation mesh in a single flow passage has about 165,000 cells, and Y+ is about 1.0. The mesh has been verified to meet the requirement of grid independence through previous work (Guo and Chu 2022), and used for many aerodynamic studies (Guo et al 2022a, b).…”
Section: Description Of the Numerical Modelmentioning
confidence: 99%
“…Gaussian distributions for flow variations have been widely applied in describing stochastic flow variations (Hosder et al 2007;Loeven et al 2007;Loeven and Bijl 2010). Because the disturbance range of uncertainty variables cannot be infinite, the truncated Gaussian distribution is more practical to describe the uncertainty, which has been accepted by many aerodynamic UQ studies (Wu et al 2017;Guo and Chu 2022). Thus, it is also employed to illustrate the variation of inlet incidences…”
Section: Evaluations Of Performance Impactmentioning
confidence: 99%
“…The verification of the mesh-independence has been studied in the previous work. 29 The node number of the computing mesh is encrypted to about 1.65E05, in which the calculated Y + is about 1. Figure 1 gives the local computational mesh of the airfoil and the accuracy verification of the numerical scheme.…”
Section: Uncertainty Modeling Of Inflow and Geometric Variationsmentioning
confidence: 99%
“…The profile error defines the normal distance between the manufactured and design profile lines, which is related to the variation of maximum thickness and LE radius. The open literatures 29,31 have respectively shown that the maximum thickness and LE variations affect the boundary-layer development. The torsion error refers to the angular difference between the manufactured and design profiles.…”
Section: Uncertainty Modeling Of Inflow and Geometric Variationsmentioning
confidence: 99%